Role of Estrogen in the Oxidation Process in Postmenopausal Osteoporosis - Elaf Mahmood Shihab (Journal of Global Pharma Technology, 2018)
Introduction: Bone exerts important functions in the body, such as locomotion, support and protection of soft tissues, calcium and phosphate storage, and harboring of bone marrow. Osteoporosis is a common metabolic bone disease characterized by reduced bone mass, micro architectural deterioration of bone tissue, and an increased risk of fragility fracture. After menopause, the period of time after a woman has experienced 12 consecutive months without menstruation called postmenopausal period. Estrogen showed to be the most important sex steroid in preventing osteoporosis in women, so estrogens modulate bone growth and turnover in vivo. Total antioxidant capacity (TAC) is the measure of the amount of free radicals scavenged by a test solution, being used to evaluate the antioxidant capacity of biological samples. Estrogens are steroid hormones that have been shown to affect numerous tissues, including reproductive tissues (such as the breast, endometrium, and vagina) and the skeletal, cardiovascular, and central nervous systems(11).The aim of the study was to evaluate the effect of estrogen therapy on the level of total antioxidant capacity in serum of postmenopausal osteoporotic women. Materials and Methods: Randomized, single blind clinical trial carried out at the Rheumatology outpatients department of Baghdad Teaching Hospital / Medical City Complex in Baghdad, Iraq from the 10th of Jan to the 12th of June 2016.The study was carried out on 24 postmenopausal women, with amenorrhea for more than 12 consecutive months. Venous blood samples (10 ml) were drawn from each patient by venipuncture .Blood samples were taken from participants at day zero of treatment as baseline and after 90 days of treatment to obtain serum for measurement of total antioxidant capacity .Total Antioxidant Capacity (TAC) Bio Assay TM Elisa Kit manufactured by US Biological. The manufacturer instructions were strictly adhered during the laboratory procedure. Results: A total of 24 osteoporosis woman patients were enrolled in this study and they consisted of two studied groups: Group A:12 postmenopausal osteoporotic women were treated by conjugated equine estrogens tablet 0.625mg (PREMARIN ®) once daily for 90 days. Group B:12 postmenopausal osteoporotic women were treated by placebo one capsule (filled with starch) daily for 90 days and served as a control group. The mean age of the patients was 56.3 ± 6.14 (range:47 – 65). The mean Body Mass Index (BMI) of the participants was 26.86 ± 2.1 (range: 22.3 – 29.4) kg/m2. On the other hand, the comparison of mean age and BMI across the two studied groups revealed no statistically significant differences, (P>0.05) .Statistics had shown that there was no significant changes between pre and post treatment in Group A or B with baseline increase from (476.35 ± 112.79) to (484.11 ± 117.67) and (471.87 ± 165.59) to (472.78 ± 184.12) respectively ( P value > 0.05).Conclusion: daily dose of 0.625 mg of estrogen therapy for 90 days duration was not proven to be effective in lowering the oxidation level following menopause in osteoporotic women.Keywords: Estrogen, Postmenopausal osteoporosis, Antioxidant.